BRIDGING THEORY AND PRACTICE: PRE-SERVICE TEACHERS’ REFLECTIVE EXPERIENCES DURINGSCHOOL VISIT PROJECTS IN TEFL CLASS - Musdalifah; Citra Dwi Safitri; Muhammad Fahri Jaya Sudding (J-Shelves of Indragiri (JSI), 2026)
This study explores pre-service teacher’s reflective experiences during school visit projects implemented in Teaching English as a Foreign Language (TEFL) classes. The study aims to investigate how school visit activities help pre-service teacher connect pedagogical theories experiential learning. Employing a qualitative descriptive design, this study involved 15 undergraduate students enrolled in a TEFL course at an Indonesian university. The participants were selected using purposive sampling because they were directly involved in the school visit project. The project was conducted in five schools representing different educational levels, including elementary school (SD), junior high school (SMP), and involved five English teacher as interview participants. The data were collected through reflective journals, classroom observation reports, questionnaire, and semi-structured interviews. The findings revealed that the school visit project provided meaningful experiential classroom practice. The Participants reported improved understanding of teaching methods, classroom management, instructional strategies, and student engagement in authentic classroom settings. The project also enhanced students’ pedagogical awareness, reflective thinking, and analytical skills. However, several challenges were identified, including limited observation time, difficulties taking observation notes, nervousness during teacher interviews, and challenges understanding classroom dynamics. The data were analyzed using thematic analysis by coding and categorizing participants’ responses into several themes related to reflective learning and pedagogical development. This study concludes that school visit projects can serve as effective experiential and reflective learning activities in TEFL teacher education.